Soil-Landscape Relationships in Kedah - A Study in Soil Genesis and Classification - Lim, Jit Sai (1991)
The genesis, classification and soil-landscape relationships of three major landscapes and fourteen soils in Kedah were studied. The BRIS soils are sandy, structureless, loose, highly leached and have a very low water holding retention and cation exchange capacity (CEC). Soils on the youngest and the oldest ridges are Entisols. Spodosols are found in the middle ridges. Podzolisation is also discussed. The marine coastal plain soils are poorly drained, clayey and have a high CEC (> 20 cmol(+)kg-l soil) due to the presence 2: 1 clay minerals. Soil formation is strongly influenced by the activities of man, parent materials, physiography, climate and sea water. The plough layer and plough sole are formed by the continual addition of organic matter and wet ploughing. Desalination is accomplished by bunding and by flushing the soils with fresh irrigation water. The influence of climate is manifested by deep vertical cracks and gypsum crystals during the dry season. Profile development improves towards the hinterland due to progressively higher physiographic positions, lower ground water table, higher leaching intensity and improved drainage. Three of the soils are Entisols (Fluvaquents) because the organic carbon at 1.25 m is greater than 0.2% although they are more appropriately classified as Inceptisols (Tropaquepts) due changes in the soil colour and the structures. A Vertisol was identified. Soils of the pediplains and the P surfaces are characterised by a lateritic layer. Lateritic soils on P surfaces in eastern Kedah have larger and more angular boulders and gravels. The gravels on the pediplain proper are finer and more rounded due to more cycles of pedimentation. Etchplains and remnants of pediplains (R.O.P.) are absent in the P/P3 surfaces and are uncommon in the pediplains. Lateritic soils in northern Kedah are Ultisols and in southern and eastern Kedah, Oxisols; this being due to differences in the parent materials and climate.